2018
DOI: 10.1007/s00296-018-4135-9
|View full text |Cite|
|
Sign up to set email alerts
|

Nurses’ roles in the management of chronic inflammatory arthritis: a systematic review

Abstract: In 2011 EULAR first published recommendations for the potential role of nurses in the management of patients with rheumatic diseases. To perform a literature update for the role of nurses in the management of chronic inflammatory arthritis (CIA) from 2010 to 2018. A systematic literature review (SLR) was performed according to the PRISMA guidelines, in accordance with the search strategies and eligibility criteria of the EULAR taskforce. The eligibility criteria were “inflammatory arthritis”, “interventions un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In the field of rheumatology, nurses have an important role in the management of chronic inflammatory arthritis (Vivienne & Michael, ) together with medical doctors and other healthcare professionals. The main treatment goal is to reduce disease activity, prevent structural damage and improve functionality and social participation (Smolen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of rheumatology, nurses have an important role in the management of chronic inflammatory arthritis (Vivienne & Michael, ) together with medical doctors and other healthcare professionals. The main treatment goal is to reduce disease activity, prevent structural damage and improve functionality and social participation (Smolen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Patient education is recommended as an integral part of disease management for people with IA (Combe et al, ; Deighton, O'Mahony, Tosh, Turner, & Rudolf, ; Dejaco et al, ; Richette et al, ; Smolen et al, ; van der Heijde et al, ; Zangi et al, ), where long‐term pharmacological treatment (Connelly et al, ) and disease activity self‐assessment are central. In addition to patient education, patients need support after attendance, often provided as follow‐up phone calls or face‐to‐face consultations (Vivienne & Michael, ).…”
Section: Introductionmentioning
confidence: 99%
“…Specialized rheumatology nurses provide advice over the phone and offer self-management, education, and counseling for patients (62)(63)(64)(65)(66)(67). In addition, they participate in disease management, monitor disease-modifying treatments, help treat comorbidities and, after special training, give intra-articular injections and prescribe drug treatments (59,(68)(69)(70)(71).…”
Section: Role Of Nursing In Rheumatologic Carementioning
confidence: 99%
“…Studies conducted on patients with rheumatoid arthritis (RA) have demonstrated that nurse-led care is widely accepted, similarly efficient, and safe as physician-led care. Additionally, from the patient’s point of view, nurse-led care is convenient and easily reachable [ 9 , 10 ]. The development and broad adoption of telehealth initiatives have the potential to create new opportunities for rheumatology nurses and improve accessibility [ 11 ].…”
Section: Introductionmentioning
confidence: 99%